2020
DOI: 10.3390/jcm9020586
|View full text |Cite
|
Sign up to set email alerts
|

Variable Responses to Corneal Grafts: Insights from Immunology and Systems Biology

Abstract: Corneal grafts interact with their hosts via complex immunobiological processes that sometimes lead to graft failure. Prediction of graft failure is often a tedious task due to the genetic and nongenetic heterogeneity of patients. As in other areas of medicine, a reliable prediction method would impact therapeutic decision-making in corneal transplantation. Valuable insights into the clinically observed heterogeneity of host responses to corneal grafts have emerged from multidisciplinary approaches, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 157 publications
1
18
0
Order By: Relevance
“…During the process of rejection, lymphatic vessels and neovascular tissues are important factors that support the immune and inflammation response, as donor antigens, inflammatory cells, and pro-inflammatory cytokines could be delivered through these vessels to the graft. For corneal graft survival, reducing neovascularization and lymphangiogenesis is vital, 43 , 44 and such reduction was confirmed in our high-risk mouse corneal grafts.…”
Section: Discussionsupporting
confidence: 73%
“…During the process of rejection, lymphatic vessels and neovascular tissues are important factors that support the immune and inflammation response, as donor antigens, inflammatory cells, and pro-inflammatory cytokines could be delivered through these vessels to the graft. For corneal graft survival, reducing neovascularization and lymphangiogenesis is vital, 43 , 44 and such reduction was confirmed in our high-risk mouse corneal grafts.…”
Section: Discussionsupporting
confidence: 73%
“…Our results showed that TNF-α, IFN-γ, IL-1β, and IL-2 levels in the aqueous humor of keratoplasty rejection cases were much higher than those in cases where the grafts survived [129][130][131][132][133] (Figure 6). Finally, as in other tissues beyond the eye, the homeostatic equilibrium of the ocular surface is critically maintained by complex and heterogeneous parainflammatory mechanisms [138][139][140]. Cross-talk between APCs, T cells, and various other immune cells plays a central role in corneal graft tolerance (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as in other tissues beyond the eye, the homeostatic equilibrium of the ocular surface is critically maintained by complex and heterogeneous parainflammatory mechanisms [138][139][140]. Cross-talk between APCs, T cells, and various other immune cells plays a central role in corneal graft tolerance (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…CNV occurs as a result of an imbalance between angiogenic and anti-angiogenic factors in favour of angiogenic molecules [29][30][31][32] . This imbalance causes pathogenic angiogenesis in CNV, which in turn activates pro-angiogenic factors including VEGF, VEGFR, and IFN-γ in the neovascularized microenvironment and strongly potentiates further development of CNV 21,33 .…”
Section: Discussionmentioning
confidence: 99%